THE PROTECTION OF HOMELESS PERSONS BY THE COURTS AND CONSTITUTIONAL TRIBUNALS - Miranda Bonilla, Haideer (2020)
The purpose of this study is to analyze the protection of vulnerable groups and, in particular, the protection that people in street situation have received, in the jurisprudence of some Constitutional or Supreme Courts of Costa Rica, Colombia and Italy; with the purpose of determining which themes have been analyzed, as well as the challenges that count from the perspective of constitutional law.